2017
DOI: 10.18287/2412-6179-2017-41-6-957-962
|View full text |Cite
|
Sign up to set email alerts
|

Image blur estimation using gradient field analysis

Abstract: Оценивание степени размытости изображения путём анализа градиентного поля Асатрян Д.Г. Компьютерная оптика, 2017, том 41, №6 957 ОЦЕНИВАНИЕ СТЕПЕНИ РАЗМЫТОСТИ ИЗОБРАЖЕНИЯ ПУТЁМ АНАЛИЗА ГРАДИЕНТНОГО ПОЛЯ Д.Г. Асатрян 1,2 1 Российско-Армянский (Славянский) университет, Ереван, Армения, 2 Институт проблем информатики и автоматизации национальной академии наук, Ереван, Армения Аннотация Оценивание степени размытости является важным шагом на пути улучшения качества изображения. В литературе предложено много подходо… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Such metrics make possible to evaluate the quality based on the image only without the reference. Part of the metrics is developed to assess the single factor affecting the quality, for example, the blurriness level [17]. Other ones claim to be universal.…”
Section: Resultsmentioning
confidence: 99%
“…Such metrics make possible to evaluate the quality based on the image only without the reference. Part of the metrics is developed to assess the single factor affecting the quality, for example, the blurriness level [17]. Other ones claim to be universal.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies have shown that the value of the statistical estimate of shape parameter η of Weibull distribution can be used as a blur measure. In [15], on simulated blur data of various images, it is shown that the value of the parameter estimate increases monotonically as the degree of blurring increases. For example, Figure 4 shows an image and its blurred patterns, with the corresponding values of parameter η.…”
Section: Applicationsmentioning
confidence: 99%
“…It is also shown in [15] that in general the parameter η can be interpreted as a measure for image structuredness.…”
Section: Applicationsmentioning
confidence: 99%
“…Such metrics make possible to evaluate the quality based on the image only without the reference. Part of the metrics is designed to assess one factor affecting the quality, for example, the blurriness level [14].…”
Section: Analysis Of the Use Of No-reference Quality Metrics For Micro-ct Imagesmentioning
confidence: 99%